Weathering crusts and their role in formation of post-kimberlite sedimentary sequences - Nikolai N. Zinchuk (Руды и металлы)
The principal suppliers of terrigenous material to forming ancient diamond placers are characterized based on the main diamond-bearing districts of the Siberian platform as an example. A special attention is paid to characteristics of the local sources of allothigenous material washed out into sedimentation basins of the period specified, the main of which were weathering crusts formed upon terrigenous-carbonate rocks, trappean formations (dolerites, tuffs, and tuffaceous rock sequences), and kimberlites. A comprehensive comparative investigation of the ancient weathering crusts upon the rocks of various chemical and mineralogical composition allowed tracing the specific features of their hypergene alteration and the typomorphic indications of the eluvial products. The same varieties of primary minerals in redeposited products of weathering of the various rocks may be differentiated at the structural level, and the secondary phyllosilicates may be identified either by occupation of the octahedral positions in their structure, or by mutual superposition of individual silicate layers, or by their polytypic character. Redeposition of the products of weathering of the rocks of various composition near the denudation areas and their predominant accumulation in freshwater basins, as well as a small thickness of the sedimentary layers formed and their insignificant burial, had determined a weak hydrodynamic impact of the environment on the allothigenous minerals (argillaceous, first of all), which did not lead to their sufficient diagenetic alteration. Therefore, the products of various types of the weathering crusts, redeposited in the ancient sedimentary sequences, retain the structural and crystal-chemical peculiarities in relation to the minerals of the eluvial rock masses, which allows tracing the ways of arrival of the terrigenous (including diamondiferous) material into the sedimentation basins.